A Comparative Study on Flavonoid Content of Cheilanthes Pteridioides (Richard.) C. Chr.1905 in Two Different Districts - Iraq - Murtadeh, Abbas; Al-Majmaie, S. Hatem; Ali, Z. A. (Al-Nahrain Journal of Science, 2024)
The studied regions were comprised of Erbil and Garmian districts, there were differences in geographic locations and habitat.  The collected ferns were from 1st  in  Mallakan region, and 2nd in Kalar region from Erbil and Garmian districts respectively. Four active compounds qualitatively (flavonoids, tannins, alkaloids and saponins) were screened in two studied regions. Flavonoid compounds screened in the Mallakan region represent four flavonoids which were: Myrectin, Kaempferole and Rutine , but in Kalar region represent: Kaempherol, Myrectin, Qurectin and Rutin. A phytochemical quantitative study revealed that total flavonoids in Kalar region (540 µg/ml) were higher than total flavonoids in the Mallakan region (280 µg/ml). The study aimed to determine the flavonoids of Cheilanthes pteridioids (Richard) C. Chr. (Pteridaceae) in two different districts North of Iraq.